Synthesis of rare sugars via epimerization catalyzed by tin-organic frameworks - Valérie Toussaint; Theresa Röper; Katarina Hricova; Irina Delidovich (Current Research in Green and Sustainable Chemistry, 2025)
Epimerization of readily available monosaccharides presents an atom-efficient approach to expand the portfolio of rare monosaccharides. Here, we report tin-organic frameworks (Sn-OF) as a highly selective catalyst for synthesis of rare monosaccharides, such as L-ribose, D-lyxose, D-talose, and L-quinovose, via epimerization reaction. Remarkable selectivity of 67–95 % for the epimerization products was achieved. The maximal yields obtained were 22 % for D-lyxose, 14 % for L-ribose, 15 % for D-talose, and 18 % for L-quinovose. Additionally, a correlation between the structure of the substrate and reaction rate was established, suggesting that the saccharides react in open-chain form, with the cis-orientation of OH-groups facilitating the epimerization. Moreover, it was shown that the catalyst can be reused in a second run. The catalytic epimerization results in a mixture of epimers, from which partial recovery of the substrate can be achieved through crystallization, as demonstrated for L-arabinose, D-galactose, and D-xylose.